Állami kitüntetések az ellenforradalom leverésében résztvevőknek, társadalombiztosítási rendelet . State Award for Persons Helping Crack the Counter-Revolution, and the Social Security Decree - Héderváry, Claire de (1958)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): Magyar Közlöny